PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PORTOFOLIO: ALTERNATIF BAHAN AJAR MATA KULIAH MATERI PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Muhamad Fakhrur Saifudin (Universitas Ahmad Dahlan, 2020)
The purpose of this research to develop a portfolio based teaching materials and test the feasibility of the portfolio based teaching materials in the course of learning materials in the Indonesian language and literature department of PGSD UAD. The type of data in the study to development is the actions, product, and documents about the planning, implementation, and evaluation of learning language and literature teaching materials Indonesia. Products validity by using the sign of curriculum specialists, materials. Data collection using observation, interview, documentation, and questionnaire. Data Validity using triangulation or data source. Data were analyzed using critical analysis that includes data reduction, and a conclusion/verification. The results of the study are as follows. (1) development of teaching materials in the form of this module developing through a needs analysis phase, product design, design validation, product revision, public testing, and improvement of product improvement. (2) the results of expert assessment and field tests demonstrated the feasibility of the product amounted to 86.5%, so it can be that Indonesian products based learning module is a very suitable portfolio